An improved acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene-based membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202410615519.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-05-17
AI Technical Summary
[0004]已经报道的耐酸型复合纳滤膜材料大多使用聚砜、聚醚砜、聚丙烯腈、聚偏氟乙烯等作为膜基材,这些基膜存在强度、化学稳定性较差等问题,大大降低了复合纳滤膜在严苛环境中的使用寿命
[0020](1)通过一种可控的界面聚合方法,使多元磺酰氯类油相单体溶液与多元胺类气相单体直接接触发生聚合反应,在聚四氟乙烯基膜表面一步构建聚磺酰胺耐酸分离层。
Smart Images

Figure CN118356816B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane separation technology, and in particular to an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene (PTFE) membrane, its preparation method, and its application. Background Technology
[0002] In recent years, membrane separation technology, as a highly efficient and environmentally friendly separation technology, has been widely used in water treatment, food processing, pharmaceuticals, and chemicals. Based on pore size, separation membranes can be classified into microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, and reverse osmosis membranes. Among them, nanofiltration membranes, as a novel pressure-driven membrane developed in recent years, have shown great potential in many fields due to their advantages such as high separation efficiency, good permeability, strong pressure resistance, controllable operation, and wide application, becoming one of the current research hotspots in membrane separation technology. The pore size of nanofiltration membranes is typically between 0.5 and 2 nanometers, with a molecular weight cutoff of 100-1000. Structurally, nanofiltration membranes mainly consist of a base membrane that provides support and a separation layer covering the surface of the base membrane. The separation layer achieves filtration and retention of ions in the water through sieving and Donnan effects. Interfacial polymerization is currently the most commonly used method for constructing a separation layer on the base membrane. It involves the polymerization reaction of two immiscible active monomer solutions at the interface, thereby forming a dense composite separation layer. In water treatment, nanofiltration membranes can efficiently separate heavy metal ions and other substances from water, offering advantages such as high efficiency and strong selectivity.
[0003] However, with the rapid development of industry, strongly acidic liquids are very common in practical separation applications, such as industrial acid extraction wastewater, acidic cleaning solutions, fermentation acidic wastewater, and acidic wastewater from the electroplating industry. When nanofiltration membranes come into contact with these strongly acidic solvents, they are prone to significant degradation, resulting in a substantial decrease in mechanical strength and an inability to maintain separation performance. The diversification and complexity of the systems to be separated place new demands on nanofiltration membranes. Therefore, developing an acid-resistant composite nanofiltration membrane with certain physicochemical stability in mixed strongly acidic wastewater to maintain long-term stable separation performance is of great significance.
[0004] Most reported acid-resistant composite nanofiltration membrane materials use polysulfone, polyethersulfone, polyacrylonitrile, and polyvinylidene fluoride as membrane substrates. These substrates suffer from poor strength and chemical stability, significantly reducing the service life of composite nanofiltration membranes in harsh environments. Although some acid-resistant modification methods have improved the acid resistance of composite materials to some extent, the modified composite nanofiltration membranes are prone to degradation to varying degrees under long-term acid erosion, lacking long-term stable acid resistance. Furthermore, the rapid polymerization reaction at the water-alkane interface leads to uncontrollable separation layer thickness and pore size distribution, further reducing the overall membrane permeate flux and separation performance. Summary of the Invention
[0005] To address the problems existing in the background art, the present invention aims to provide an acid-resistant composite nanofiltration membrane based on an improved polytetrafluoroethylene (PTFE) membrane, its preparation method, and its applications. The method of the present invention features a simple preparation process, controllable interfacial polymerization reaction, and maintains high permeability flux and separation performance in mixed strongly acidic waste liquids.
[0006] The technical solution adopted in this invention is as follows, including the following preparation steps:
[0007] Step S1: First, add the polysulfonyl chloride monomer to the organic solvent and stir until the polysulfonyl chloride monomer is completely dissolved to prepare an oil phase monomer solution with a concentration of 0.05-0.3wt%.
[0008] Step S2: Add 0.5g-2.5g of polyamine monomer to the bottom of the volatilization instrument, then install the hydrophobic polytetrafluoroethylene membrane on the volatilization instrument, and then immerse the entire volatilization instrument in a water bath at 30-60℃ to volatilize the polyamine monomer into the gas phase. The volatilization time is 5-25min.
[0009] Specifically, the evaporation apparatus comprises two separable parts: an upper part, a hollow glass cylinder open at both ends, and a lower part, a glass container with a vent valve, open at the top and closed at the bottom. The lower end of the hollow glass cylinder is detachably connected to the upper end of the glass container. The polyamine monomer is located at the bottom of the glass container, and a polytetrafluoroethylene (PTFE) membrane is horizontally installed at the connection point between the hollow glass cylinder and the glass container. Step S2, which involves adding the PTFE membrane and polyamine monomer, involves adding the polyamine monomer to the bottom of the lower glass container, then placing the PTFE membrane flat on top of the glass container, placing the upper hollow glass cylinder on top of the PTFE membrane, aligning the two parts, and securing them with clamps, thus pressing the PTFE membrane between the upper and lower parts of the evaporation apparatus.
[0010] Step S3: Pour the oil phase monomer solution obtained in step S1 from above the evaporation apparatus and immerse the polytetrafluoroethylene membrane. On the lower surface of the polytetrafluoroethylene membrane, the poured oil phase monomer solution comes into contact with the gas phase polyamine monomer and undergoes a polymerization reaction at the contact interface, thereby forming a polysulfonamide separation layer. Remove the polytetrafluoroethylene membrane with the polysulfonamide separation layer attached from the evaporation apparatus and place it in an oven at 60-80℃ for heat curing treatment for 5-20 minutes to obtain the initially formed acid-resistant composite nanofiltration membrane.
[0011] Step S4: Completely immerse the acid-resistant composite nanofiltration membrane obtained in step S3 in the prepared sodium dodecylbenzenesulfonate aqueous solution, let it stand for 10-30 minutes, then remove the acid-resistant composite nanofiltration membrane and air dry it to improve the permeation performance of the composite nanofiltration membrane, and obtain the finished acid-resistant composite nanofiltration membrane.
[0012] In step S1, the polysulfonyl chloride monomer is at least one of the following reagents: 1,3-benzene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride, 2,4,6-trimethylbenzene sulfonyl chloride, 1,6-naphthalene disulfonyl chloride, 2,6-naphthalene disulfonyl chloride, and 1,3,6-naphthalene trisulfonyl chloride.
[0013] The organic solvent in step S1 is at least one of the following solvents: n-hexane, cyclohexane, cyclopentane, n-octane, isooctane, ethylcyclohexane, hydrocarbon oil, toluene, ethyl acetate, etc.
[0014] The polyamine monomer in step S2 is at least one of the following reagents: piperazine, 2,2-dimethylpiperazine, 2,3-diaminopiperazine, ethylenediamine, triethyltetramine, tetraethylpentamine, and polyethyleneimine.
[0015] In step S3, the reaction time for the polymerization reaction between the oil phase monomer solution and the gas phase polyamine monomer at the contact interface is 0.5-4 min.
[0016] The mass ratio of sodium dodecylbenzenesulfonate aqueous solution in step S4 is 2-10 wt%.
[0017] The acid-resistant composite nanofiltration membrane was prepared using the method described above.
[0018] The acid-resistant composite nanofiltration membrane described herein is used in waste battery recycling, industrial wastewater treatment, radioactive element separation, environmental remediation, and precious metal recovery.
[0019] The advantages of this invention are:
[0020] (1) A controllable interfacial polymerization method is used to directly contact the oil phase monomer solution of polysulfonyl chloride with the gas phase monomer of polyamine to carry out a polymerization reaction, thereby constructing a polysulfonamide acid-resistant separation layer on the surface of polytetrafluoroethylene film in one step.
[0021] (2) Using polytetrafluoroethylene (PTFE), which is resistant to acids and alkalis, various organic solvents, and has high mechanical strength, as the supporting substrate for the composite nanofiltration membrane significantly improves the overall acid resistance and stability of the composite nanofiltration membrane. Furthermore, a polysulfonamide separation layer is constructed. Due to the electron-withdrawing effect of the sulfur atom, the polarity of the SO bond in polysulfonamide is much smaller than that of the CO bond, thus determining that oxygen is not easily attacked by protons under acidic conditions. In addition, the strong conjugation in the polysulfonamide molecular structure gives it excellent hydrolysis resistance, significantly improving the acid resistance of the composite nanofiltration membrane and providing strong stability, preventing its acid resistance from deteriorating during long-term use.
[0022] (3) Furthermore, in traditional interfacial polymerization methods, the oil phase and aqueous phase monomer solutions come into contact at the immiscible liquid-liquid interface and undergo rapid interfacial polymerization. Because the polymerization reaction time is difficult to control, a thick separation layer is easily formed rapidly on the polytetrafluoroethylene membrane surface, severely affecting the filtration and permeation effect of the composite nanofiltration membrane. This invention optimizes the preparation process by replacing traditional liquid-liquid polymerization with a controllable interfacial polymerization method, allowing the sublimated amine layer to directly contact the alkane-containing sulfonyl chloride. This process is anhydrous, eliminating potential side reactions caused by the aqueous phase, effectively suppressing the hydrolysis of the acyl chloride, and improving the density of the resulting separation layer. Simultaneously, because the reaction kinetics during the interfacial polymerization of gaseous amine and oil phase solution are slow, the formation process of the separation layer is easier to control. The thickness and pore size of the separation layer can be adjusted by the reaction time, thereby imparting controllable permeation flux and separation selectivity.
[0023] (4) In this preparation method, a superior permeation flux can be achieved through a controllable interfacial polymerization reaction. By optimizing the preparation process, optimal filtration permeation capacity can be achieved, thereby further reducing the additional pressure-driven energy consumption required for nanofiltration membranes to improve separation rates. This composite nanofiltration membrane significantly improves acid resistance while maintaining controllable permeation flux and long-term stability, providing a new preparation method for separation membrane materials used in harsh environments.
[0024] The acid-resistant composite nanofiltration membrane prepared by the method of the present invention can achieve performance optimization and material multifunctionality by using other polymer monomers, grafting other functional groups, and loading polymers.
[0025] The acid-resistant composite nanofiltration membrane prepared by this invention has multiple application fields, including: applications in complex environments such as the metal industry, mining, petroleum industry, environmental remediation, waste battery and precious metal recycling.
[0026] The beneficial effects of this invention are as follows:
[0027] 1. The method of this invention is simple, controllable in preparation, and low in energy consumption, requiring a wide variety of raw materials from diverse sources. The prepared composite nanofiltration membrane uses a polytetrafluoroethylene microporous membrane instead of traditional polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, etc., as the supporting substrate, which greatly improves the overall mechanical strength and acid resistance of the membrane.
[0028] 2. A controllable interfacial polymerization method is used to directly contact a polysulfonyl chloride oil-phase monomer solution with a polyamine gas-phase monomer, allowing the polymerization reaction to occur directly at the interface, forming a polysulfonamide separation layer in one step. This method avoids side reactions caused by water and facilitates controllable adjustment of the polysulfonamide separation layer thickness and pore size, resulting in adjustable permeation flux and separation selectivity.
[0029] 3. By utilizing the stability of the SO bond in polysulfonamide under acidic conditions and the strong conjugation effect in its molecular structure, the composite nanofiltration membrane possesses excellent acid resistance and hydrolysis resistance, as well as strong structural stability. Its acid resistance is not easily degraded during long-term use.
[0030] 4. The acid-resistant composite nanofiltration membrane prepared by the method of this invention exhibits long-term stable acid resistance and high mechanical strength during use. It also possesses excellent filtration permeation flux and separation performance, making it suitable for recovering and separating valuable metal ions from mixed strongly acidic waste liquids in fields such as metal industry, mining, petroleum industry, environmental remediation, waste battery and precious metal recycling, and has broad application prospects. Attached Figure Description
[0031] Figure 1 A schematic diagram of the reaction principle for constructing an acid-resistant composite nanofiltration membrane in one step;
[0032] Figure 2 The graph shows the changes in metal rejection rate and water flux of composite nanofiltration membranes prepared using different sulfonyl chloride monomers before and after acid treatment. The sulfonyl chloride monomers include: 1,3-benzene disulfonyl chloride (A), 1,3,5-benzene trisulfonyl chloride (B), 2,4,6-trimethylbenzene sulfonyl chloride (C), 1,6-naphthalene disulfonyl chloride (D), and 2,6-naphthalene disulfonyl chloride (E).
[0033] Figure 3 The graph shows the rate of change in metal rejection and water flux of composite nanofiltration membranes prepared using different masses of piperazine before and after acid treatment;
[0034] Figure 4 The graph shows the changes in metal rejection rate and water flux of composite nanofiltration membranes prepared under different interfacial polymerization reaction times before and after acid treatment.
[0035] Figure 5The graph shows the rate of change in metal rejection and water flux of composite nanofiltration membranes prepared using sodium dodecylbenzenesulfonate aqueous solutions with different mass ratios before and after acid treatment. Detailed Implementation
[0036] The present invention will be described in detail below with reference to specific implementation examples. These examples will help those skilled in the art to further understand the present invention, but do not limit the present invention in any way.
[0037] The present invention will be described in more detail through the following embodiments, but the embodiments do not constitute a limitation of the present invention.
[0038] The embodiments of the present invention are as follows:
[0039] Example 1
[0040] Step S1: First, add 1,3-benzenedisulfonyl chloride to n-hexane solvent and stir until 1,3-benzenedisulfonyl chloride is completely dissolved to prepare an oil phase monomer solution with a concentration of 0.2 wt%.
[0041] Step S2: Add 1g of piperazine to the bottom of the volatilization instrument, then install the hydrophobic polytetrafluoroethylene membrane on the volatilization instrument, and then immerse the entire volatilization instrument in a 40°C water bath to volatilize the piperazine into the gas phase for 10 minutes, forming a stable gaseous environment in the cavity below the base membrane.
[0042] Specifically, such as Figure 1 As shown, the evaporation apparatus comprises two separable parts: an upper part consisting of a hollow glass cylinder open at both ends, and a lower part consisting of a glass container with a vent valve, open at the top and closed at the bottom. The lower end of the hollow glass cylinder is detachably connected to the upper end of the glass container. The polyamine monomer is located at the bottom of the glass container, and a polytetrafluoroethylene (PTFE) membrane is horizontally installed at the connection point between the hollow glass cylinder and the glass container.
[0043] Step S3: Pour the oil-phase monomer solution obtained in step S1 from above the evaporation apparatus and completely immerse the polytetrafluoroethylene (PTFE) membrane. On the lower surface of the PTFE membrane, the poured oil-phase monomer solution comes into contact with the gaseous piperazine and undergoes a polymerization reaction at the contact interface, thereby forming a polysulfonamide separation layer on the lower surface of the PTFE membrane. After 1 minute, remove the PTFE membrane with the polysulfonamide separation layer attached from the evaporation apparatus and place it in an oven at 60°C. After heat curing for 10 minutes, a preliminarily formed dry acid-resistant composite nanofiltration membrane is obtained. Next, dissolve sodium dodecylbenzenesulfonate in deionized water to prepare an 8% (w / w) sodium dodecylbenzenesulfonate aqueous solution as an activation and modification solution.
[0044] Step S4: The acid-resistant composite nanofiltration membrane obtained in step S3 is completely immersed in the prepared sodium dodecylbenzenesulfonate aqueous solution (i.e., activation and modification solution). After standing for 20 minutes, the acid-resistant composite nanofiltration membrane is taken out and placed in the air to air dry naturally to improve the permeability of the composite nanofiltration membrane and obtain the finished acid-resistant composite nanofiltration membrane.
[0045] Acid resistance test: The finished acid-resistant composite nanofiltration membrane was immersed in a 20% sulfuric acid solution at 25℃ for 72 hours, followed by repeated rinsing with deionized water until the pH of the eluent stabilized. The separation performance and water flux of the finished acid-resistant composite nanofiltration membrane before and after acid treatment were tested. The metal rejection rate and water flux before acid treatment were measured to be 97.23% and 20.82 L·m, respectively. -2 ·h -1 ·bar -1 The metal rejection rate and water flux after acid treatment were 21.17%.
[0046] Examples 2-5
[0047] Examples 2-5 used 1,3,5-benzenetrisulfonyl chloride, 2,4,6-trimethylbenzenesulfonyl chloride, 1,6-naphthalenedisulfonyl chloride, and 2,6-naphthalenedisulfonyl chloride as sulfonyl chloride monomers, respectively, with other conditions the same as in Example 1. The results are shown in Table 1 below. Figure 2 .
[0048] Table 1. Results of acid resistance performance in Examples 2-5
[0049]
[0050] The results showed that the acid-resistant composite nanofiltration membrane prepared by the method of the present invention exhibited excellent acid resistance, with changes in metal rejection rate and water flux of less than 5% before and after acid treatment. The membrane with 1,3-benzenedisulfonyl chloride as the oil phase monomer showed the best acid resistance.
[0051] Examples 6-9
[0052] In Examples 6-9, the mass of piperazine was 0.5g, 1.5g, 2g, and 2.5g, respectively, with the other conditions the same as in Example 1. The results are shown in Table 2 below. Figure 3 .
[0053] Table 2. Results of acid resistance performance in Examples 6-9
[0054]
[0055]
[0056] The results showed that the acid-resistant composite nanofiltration membrane prepared by the method of this invention exhibited excellent acid resistance, with changes in metal rejection rate and water flux both below 5% before and after acid treatment. Furthermore, the acid resistance was best when the piperazine mass was 1g.
[0057] Examples 10-13
[0058] In Examples 10-13, the interfacial polymerization reaction times were 0.5 min, 2 min, 3 min, and 4 min, respectively, with other conditions the same as in Example 1. The results are shown in Table 3 below. Figure 4 .
[0059] Table 3. Results of acid resistance performance in Examples 10-13
[0060]
[0061] The results showed that the acid-resistant composite nanofiltration membrane prepared by the method of this invention exhibited excellent acid resistance, with changes in metal rejection rate and water flux both below 5% before and after acid treatment. Furthermore, the acid resistance was best when the interfacial polymerization reaction time was 1 min.
[0062] Examples 14-17
[0063] In Examples 14-17, the mass ratios of sodium dodecylbenzenesulfonate aqueous solution were 2.0 wt%, 4.0 wt%, 6.0 wt%, and 10.0 wt%, respectively, with the other conditions being the same as in Example 1. The results are shown in the table below. Figure 5 .
[0064] Table 4. Results of acid resistance performance in Examples 14-17
[0065]
[0066] The results showed that the acid-resistant composite nanofiltration membrane prepared by the method of this invention exhibited excellent acid resistance, with changes in metal rejection rate and water flux both below 5% before and after acid treatment. Furthermore, the acid resistance was best when the mass ratio of sodium dodecylbenzenesulfonate aqueous solution was 8.0 wt%.
[0067] The composite nanofiltration membrane prepared by this invention has excellent acid resistance and hydrolysis resistance, as well as strong structural stability. Its acid resistance is not easily degraded during long-term use.
[0068] While the specific embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention, and modifications or variations without creative effort are still within the protection scope of the present invention.
Claims
1. A method for preparing an acid-resistant composite nanofiltration membrane based on a modified polytetrafluoroethylene (PTFE) vinyl membrane, characterized in that, Includes the following steps: Step S1: First, add the polysulfonyl chloride monomer to the organic solvent and stir until the polysulfonyl chloride monomer is completely dissolved to prepare an oil phase monomer solution with a concentration of 0.05-0.3wt%. Step S2: Add 0.5g-2.5g of polyamine monomer to the bottom of the volatilization instrument, then install the hydrophobic polytetrafluoroethylene membrane on the volatilization instrument, and then immerse the entire volatilization instrument in a water bath at 30-60℃ to volatilize the polyamine monomer into the gas phase. The volatilization time is 5-25min. Step S3: Pour the oil phase monomer solution obtained in step S1 from above the evaporation apparatus and immerse the polytetrafluoroethylene membrane. On the lower surface of the polytetrafluoroethylene membrane, the poured oil phase monomer solution comes into contact with the gas phase polyamine monomer and undergoes a polymerization reaction at the contact interface, thereby forming a polysulfonamide separation layer. Remove the polytetrafluoroethylene membrane with the polysulfonamide separation layer attached from the evaporation apparatus and place it in an oven at 60-80℃ for heat curing treatment for 5-20 minutes to obtain the initially formed acid-resistant composite nanofiltration membrane. Step S4: Immerse the acid-resistant composite nanofiltration membrane obtained in step S3 completely in the prepared sodium dodecylbenzenesulfonate aqueous solution, let it stand for 10-30 minutes, then take out the acid-resistant composite nanofiltration membrane and air dry it to obtain the finished acid-resistant composite nanofiltration membrane.
2. The method for preparing an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene vinyl membrane improved according to claim 1, characterized in that: In step S1, the polysulfonyl chloride monomer is at least one of 1,3-benzene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride, 2,4,6-trimethylbenzene sulfonyl chloride, 1,6-naphthalene disulfonyl chloride, 2,6-naphthalene disulfonyl chloride, and 1,3,6-naphthalene trisulfonyl chloride.
3. The method for preparing an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene vinyl membrane improved according to claim 1, characterized in that: The organic solvent in step S1 is at least one of n-hexane, cyclohexane, cyclopentane, n-octane, isooctane, ethylcyclohexane, hydrocarbon oil, toluene, and ethyl acetate.
4. The method for preparing an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene vinyl membrane improved according to claim 1, characterized in that: The polyamine monomer in step S2 is at least one of piperazine, 2,2-dimethylpiperazine, 2,3-diaminopiperazine, ethylenediamine, triethyltetramine, tetraethylpentamine, and polyethyleneimine.
5. The method for preparing an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene vinyl membrane improved according to claim 1, characterized in that: In step S3, the reaction time for the polymerization reaction between the oil phase monomer solution and the gas phase polyamine monomer at the contact interface is 0.5-4 min.
6. The method for preparing an acid-resistant composite nanofiltration membrane based on a polytetrafluoroethylene vinyl membrane improved according to claim 1, characterized in that: The mass ratio of sodium dodecylbenzenesulfonate aqueous solution in step S4 is 2-10 wt%.
7. An acid-resistant composite nanofiltration membrane, characterized in that: The acid-resistant composite nanofiltration membrane is prepared using the preparation method described in any one of claims 1 to 6.
8. The application of the acid-resistant composite nanofiltration membrane obtained by the preparation method according to any one of claims 1-6, characterized in that: The acid-resistant composite nanofiltration membrane described herein is used in waste battery recycling, industrial wastewater treatment, radioactive element separation, environmental remediation, and precious metal recovery.
Citation Information
Patent Citations
Thin film composite membrane with nano-sized bubbles having enhanced membrane permeability, preparation methods and uses thereof
CN110545903A
Acid-resistant composite nanofiltration membrane and preparation method thereof
CN112642305A
